2006
DOI: 10.1161/01.hyp.0000214867.35632.0e
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic Brain Injury Is Exacerbated in Mice Lacking the Kinin B2 Receptor

Abstract: Abstract-Kallikrein cleaves low molecular weight kininogen to generate vasoactive kinins, which bind to the kinin B2 receptor, triggering a host of biological effects. Kallikrein gene delivery has been shown previously to reduce ischemia/reperfusioninduced cerebral infarction. In this study, we tested the hypothesis that the kinin B2 receptor plays a protective role in ischemic brain injury using kinin B2 receptor gene knockout (B2R-KO) mice subjected to middle cerebral artery occlusion (MCAO). The mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 39 publications
7
54
1
Order By: Relevance
“…12 Differences in the time of brain ischemia (45 min vs 60 min) obviously did not account for the divergent results, because we also observed identical infarct volumes after 45 minutes of tMCAO at day 1 in WT and B2R KO mice (not shown). In obvious contrast to Gröger et al, 12 Xia et al 53 postulated that postischemic brain injury is exacerbated in mice lacking the B2R. Numerous studies did not find a detrimental effect of B2R deficiency or blockade on stroke outcome.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…12 Differences in the time of brain ischemia (45 min vs 60 min) obviously did not account for the divergent results, because we also observed identical infarct volumes after 45 minutes of tMCAO at day 1 in WT and B2R KO mice (not shown). In obvious contrast to Gröger et al, 12 Xia et al 53 postulated that postischemic brain injury is exacerbated in mice lacking the B2R. Numerous studies did not find a detrimental effect of B2R deficiency or blockade on stroke outcome.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies did not find a detrimental effect of B2R deficiency or blockade on stroke outcome. 12,54,55 Infarct size in WT mice after 90 minutes of MCAO was surprisingly small in the study by Xia et al, 53 whereas the B2R KO mice had developed infarcts that were the size that one would usually expect in WT mice after 90 minutes of tMCAO. We and others 27,28,55,56 could demonstrate that 60 minutes of occlusion of the MCA already causes infarct volumes between 50 and 80 mm 3 at day 1 after MCAO, eg, in C57BL/6, SV129, or Swiss mice.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, several studies have suggested that agonism of the B1R and B2R may have different effects on the severity of I/R injury (21)(22)(23). In contrast, lack of the B1R (42) or B2R (43) aggravates the I/R injury in the heart and brain of mice, whereas adenovirus-mediated gene transfer of tissue kallikrein protects against ischemic stroke in rats (44). Transgenic expression of tissue kallikrein in mice attenuates ischemic cardiac damage (45), whereas tissue kallikrein knockout in mice aggravates the damage (24).…”
Section: Discussionmentioning
confidence: 99%
“…Neurological deficit scores were determined at 24 h, 7 days and 14 days after MCAO as previously described [27] : no neurological deficit (value=0); left forelimb flexion when suspended by the tail or failure to extend right forepaw fully (value=1); left shoulder adduction when suspended by the tail (value=2); reduced resistance to lateral push toward the left side (value=3); spontaneous movement in all directions with circling to the left exhibited only if pulled by tail (value=4); circle or walk spontaneously only to the left (value=5); walk only when stimulated (value=6); no response to stimulation (value=7); and stroke-related death (value=8).…”
Section: Neurological Deficit Scoresmentioning
confidence: 99%